Sales force deployment by mathematical programming - Knut Haase (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1999)
The sales force deployment problem is considered which arises in many selling organizations. As a solution a novel mixed-integer formulation is introduced which is specifically characterized by an infinite number of variables. A column generation approach is proposed to obtain upper and lower bounds. The associated subproblem is solved analytically. A computational study shows that the approach outperforms recently introduced approaches.
Keywords: 650; Marketing models; sales force sizing; salesperson location; sales territory alignment; sales resource allocation; nonlinear mixed-integer programming; column generation; Handelsvertretung; Personaleinsatzplanung; Betriebliche Standortwahl; Mathematische Optimierung; Theorie